The Signaling Mechanism of TGF-β Induced Bovine Mammary Epithelial Cell Apoptosis - He-Shuang Di; Li-Gang Wang; Gen-Lin Wang; Lei Zhou; Yuan-Yuan Yang (Asian-Australasian Journal of Animal Sciences, 2012)
The present study showed that Transforming growth factor beta 1 (TGF-β1) can induce apoptosis of bovine mammary epithelial cells. This apoptosis was also observed with phosphorylation of Smad2/3 within 0.5–2 h. Afterwards the signal transferred into the nucleus. Moreover, intracellular free Ca2+ concentration was significantly elevated as well as Caspase-3 activated and DNA lysised, thereby inducing the programmed cell death. This signaling pathway of TGF-β1 was blocked by SB-431542 (10−2 μM) via inhibiting ALK-5 kinase activity, which thus reversed the anti-proliferation and apoptosis effect of TGF-β1 in mammary epithelial cells. These results indicated that TGF-β1 induced apoptosis of bovine mammary epithelial cells through the ALK-5-Smad2/3 pathway, which plays an important role in inhibiting survival of mammary epithelial cells. Moreover, intracellular Ca2+ also played a critical role in TGF-β1-induced cell apoptosis.